Systematic review of virtual live tourism / Farah Azreen Ahmad and Faiz Izwan Anuar - Ahmad, Farah Azreen; Anuar, Faiz Izwan (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study published academic works of literature regarding virtual live tourism from 2019 to 2023 were collected from academic and scholar databases. The demanding and open retrieval of pertinent articles for this study is guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) approach. From 52 articles identified through this method, the study focused on distilling insights from the top 10 articles that are most impactful in the field of virtual live tourism. This study serves as a entry point to a comprehensive understanding of virtual live tourism about main ideas, the advantages, and challenges, also addressed gaps in understanding. These gaps provide avenues for future research and exploration, beckoning researchers to delve deeper into uncharted territories and contribute to the evolving body of knowledge in this field.